Production theory: Accounting for firm heterogeneity and technical change - Giovanni Dosi; Marco Grazzi; Luigi Marengo; Simona Settepanella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
The paper presents a new framework to assess firm level heterogeneity and to study the rate and direction of technical change. Building on the analysis of revealed short-run production functions by Hildenbrand (1981), we propose the (normalized) volume of the zonotope composed by vectors-firms in a narrowly defined industry as an indicator of inter-firm heterogeneity. Moreover, the angles that the main diagonal of the zonotope form with the axes provides a measure of the rates and directions of technical change over time. The proposed framework can easily account for n-inputs and m-outputs and, crucially, the measures of heterogeneity and technical change do not require many of the standard assumptions from production theory.
Keywords: D24; D61; C67; C81; O30; 330; Production theory; Heterogeneous firms; Activity Analysis; Technical change; Zonotopes; Production functions